STUDENT PERCEPTION ABOUT HIV / AIDS WITH THE STIGMATIZATION OF PLWHA - Pius A. L. Berek; Maria Dominggas Taus; Maria Huring; Christina Anugrahini (Program Studi Keperawatan, Universitas Timor, 2020)
Cases of HIV / AIDS until now is increasing and has not found a cure. Listed as one of the most deadly diseases. The cause of this disease because of sex is not healthy, drug users using needles infected with HIV / AIDS, blood transfusions, babies born to positive mothers infected with HIV / AIDS. Their underlying cause of the disease is that there are some people who have a negative perception so that they will give a stigma for people living with HIV. It also extended to the campus community. This study Aimed to identify the relationship between the student persespsi with stigmatization of PLWHA. The approach used is quantitative approach with cross sectional study design. Reviews These samples included 236 students. Data analysis using chi square. Based on test results Obtained statistical value of p = 0.000, it can be concluded that there is a correlation between students' perceptions about HIV / AIDS with the stigmatization of PLWHA. From the results Obtained by analysis of the value OR = 5.844, it means that students who have positive perceptions about HIV / AIDS have the opportunity to give 5,844 times stigmatization for people living with HIV than students who have a negative perception. Suggestion: it is Necessary to access the latest information on HIV / AIDS in order to Broaden so as to change the wrong perceptions about HIV / AIDS so that no stigma for people living with HIV